IDENTIFIKASI TITIK RAWAN KECELAKAAN (BLACK SPOT) DI DAERAH KECAMATAN WAWOTOBI, KABUPATEN KONAWE (STUDI KASUS: JALAN WOLTER MOGINSIDI-JALAN DIPENEGORO) - Masnur Posimbi; La Welendo; La Ode Muhammad Nurrakhmad Arsyad (Media Konstruksi : Jurnal Ilmiah Teknik Sipil, 2018)
Konawe Regency is one of the second –level regions in the southeast sulawesi province, the capital city of kabupaten is located in unaaha which is formed based on law number 29  of 1959 which has an area of 16,480 km,with a population of 2000 at 443,911 inhabitants.data from konawe district police obtain information that in the past five years there has been an increase is the number of accidents. Requesting data from related parties (satlantas of konawe police station) about the nember and level of accidents in the wolter monginsidi –road diponegoro for the last five yearsas secondary data. While the points to traffic accidents (black sports ) include, the intersection of there wawotobi posts, and the intersection of four wawotobi police station.